Mediating Role of Knowledge Sharing in Increasing Innovative Work Behavior in the Mandiri Inhealth Yogyakarta - Salsabila, Tiara Aulia; Mardiana, Tri (Universitas Mercu Buana, 2025)
This study aims to examine and analyze the mediating role of knowledge sharing in the relationship between organizational justice and employees’ innovative work behavior at the service office of PT Asuransi Jiwa Inhealth Indonesia in Yogyakarta. This research adopts a quantitative approach. The analytical method employed is path analysis using SmartPLS 4. The study population consisted of 174 employees, with a sample of 121 respondents selected through proportional stratified random sampling. The findings reveal that organizational justice positively and significantly affects both innovative work behavior and knowledge sharing. Furthermore, knowledge sharing also has a positive and significant effect on innovative work behavior. It is also found that knowledge sharing acts as a mediator in the relationship between organizational justice and innovative work behavior.